Auf den Hund gekommen : Von Menschen und Tieren. - Brus, Johannes; Dichter, Claudia; Golinski, Hans Günter; Hamm, Peter; Lange-Müller, Katja; Malsch, Friedemann; Posca, Claudia; Schella, Wolfgang; Schwalm, Hans-Jürgen; Thiel, Heinz; Ullrich, Ferdinand; Zola, Emile; et al. (Recklinghausen : Kunsthalle Recklinghausen, 1997)
Brus, Johannes ; Grzyb, Ryszard ; Herzog, Frank ; Hüppi, Johannes ; Ikemura, Leiko ; Herzog, Franz ; Hüppi, Johannes ; Ikemura, Leiko ; Kamlander, Franz ; Langheimer, Die ; Neumann, Hartmut ; Ro, Eun Nim ; Scheib, Hans
biografie
Auf den Hund gekommen : Von Menschen und Tieren, Kunsthalle Recklinghausen, 16. Februar bis 31. März 1997
Duits
boek